Preventive Effects of Intrauterine Injection of Bone Marrow-Derived Mesenchymal Stromal Cell-Conditioned Media on Uterine Fibrosis Immediately after Endometrial Curettage in Rabbit - Sanaz Bazoobandi; Nader Tanideh; Farhad Rahmanifar; Shahrokh Zare; Omid Koohi-Hosseinabadi; Iman Razeghian-Jahromi; Mehdi Dianatpour; Masoumeh Ahmadi; Arezoo Khoradmehr; Iraj Nabipour; Zahra Khodabandeh; Amin Tamadon (Stem Cells International)
Uterine fibrosis is an acquired disorder leading to menstrual irregularities, implantation impairment, and abortion. Mesenchymal stromal cells (MSCs) have antifibrotic properties through chemokine secretion. MSC-conditioned media (MSC-CM) contain paracrine components—exosomes—with a great potential for repairing damaged tissue or preventing fibrosis. The main goal of this study was to evaluate the preventive effects of bone marrow-derived MSC-CM (BM-MSC-CM) on uterine fibrosis after uterine curettage in rabbits. This study included 12 female rabbits (24 uterine horns in total). Excised uteri of each of the 12 female rabbits were randomly divided into four groups of intact negative control, curettage positive control, BM-MSC injection, and BM-MSC-CM injection in the way that two corresponding uteri from a rabbit were allocated to different groups. The MSC-CM were collected from cultivated BM-MSCs 48 hours after having been washed three times and replaced in serum-free media. Through a surgical approach, the caudal parts of the uteri were submitted to traumatic endometrial curettage, except for the intact negative uteri. After suturing the uterine walls, BM-MSCs or BM-MSC-CM were injected in the curettage site. Endometrial regeneration was histologically evaluated 30 days after treatment. Based on the evaluation of histomorphometric indices, curettage with or without preventive injections increased the growth of endometrial layers. However, the amount of fibrotic tissue in the CM and the BM-MSC injection groups was the same as the normal control groups, and all were less than the curettage group. A single injection of CM of MSCs after 30 days prevented the fibrotic tissue formation induced by curettage in endometrial layers of rabbits. Injecting BM-MSC-CM immediately after curettage prevented and reduced the uterine fibrosis similar to BM-MSCs in a rabbit model.